Jews, Gentiles, and ethnic reconciliation : Paul's Jewish identity and Ephesians - Yee, Tet-Lim N. (Cambridge ; New York : Cambridge University Press, 2005)
Much recent scholarship has focused on Paul's insistence on Gentile membership of the people of God equally with Jews. This book contributes to the continuing reassessment of Christian and Jewish self-understanding during the latter decades of the first century and reveals how a distinctively Jewish world view underlies Ephesians 2.
Cover; Half-title; Series-title; Title; Copyright; Dedication; CONTENTS; FOREWORD; PREFACE; ABBREVIATIONS; 1 Introduction; 2 CONTINUITY OR DISCONTINUITY? THE NEW PERSPECTIVE ON EPHESIANS, WITH REFERENCE TO EPHESIANS 2.1-10; 3 'YOU WHO WERE CALLED THE UNCIRCUMCISION BY THE CIRCUMCISION': JEWS, GENTILES AND COVENANTAL ETHNOCENTRISM ... ; 4 'HE IS OUR PEACE': CHRIST AND ETHNIC RECONCILIATION (EPHESIANS 2.14-18); 5 ISRAEL AND THE NEW TEMPLE (EPHESIANS 2.19-22); 6 SUMMARY AND CONCLUSIONS; SELECT BIBLIOGRAPHY; SUBJECT INDEX; INDEX OF SCRIPTURES AND OTHER ANCIENT WRITINGS.
Includes bibliographical references (pages 229-260) and indexes.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Bible. -- Criticism, interpretation, etc; Bible -- Critique, interprétation, etc; Paulus, -- Apostel, -- ca. 1. Jh; Paulus <Apostel>; Epheserbrief 2.; Jews in the New Testament; Gentiles in the New Testament; Juifs dans le Nouveau Testament; Gentils dans le Nouveau Testament; RELIGION -- Biblical Studies -- New Testament; RELIGION -- Biblical Studies -- Paul's Letters; Gentiles in the New Testament; Jews in the New Testament; Heidenchristentum; Judenchristentum; Christentum; Ethnische Identität; Heidentum; Juden; Judentum; Religiöse Identität; Efeziërs (bijbelboek); Joden; Heidenen; Electronic books; Criticism, interpretation, etc